Peran Konten Interaktif Dalam Pemasaran Digital Dan Pengaruhnya Terhadap Keterlibatan Pengguna: Studi Kasus Netflix - Selvy Dian Nita; Mirzam Arqy Ahmadi (FKIP - Universitas Pahlawan Tuanku Tambusai, 2024)
In today’s digital era, the media and entertainment industry has undergone significant changes in how content is produced, distributed, and consumed. One prominent innovation is the use of interactive content, allowing users to directly participate in the media experience, especially on streaming platforms like Netflix. Interactive content has become an effective tool in enhancing user engagement, strengthening brand loyalty, and creating more personalized and dynamic experiences. This research aims to analyze the influence of interactive content in digital marketing on user engagement, with a case study on the Netflix platform. The study uses a qualitative method with a literature review approach, analyzing various scholarly journals and articles from 2019 to 2024 relevant to the topics of interactive content and user engagement. Thematic analysis is conducted using user engagement theory as the main theoretical framework. The findings show that interactive content, such as Netflix's interactive episodes, can increase users' emotional, cognitive, and behavioral engagement, ultimately impacting brand loyalty and user satisfaction. The study also reveals that personalization and gamification in interactive content play a crucial role in extending interaction duration and improving user retention. This research is expected to serve as a reference for companies seeking to optimize interactive content-based digital marketing strategies to build long-term relationships with customers.